The Measurement of Electromagnetic wave Emitted from Home Appliance by Milligauss meter - Shareef, Najlaa R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The appliance of milligauss meter was designed by Qusay Ismail to measure the induce of electromagnetic field for home appliance which are put at a distance from milligauss meter (15-30-60)cm .The results showed some appliance has recorded higher than normal acceptable level of electromagnetic radiation emissions and produced radiation of (350650)milligauss as for the rest of appliances has recorded values which are ranged between (1200)milligauss ,laptop was recorde radiation generally lower than from desktop and computer moniter (CRT).The radiation ,intensity decrease with increasing distance.